Virtue ethics in the conduct and governance of social science research - Emmerich, Nathan (Advances in research ethics and integrity ;, 2018)
This collection focuses on virtue theory and the ethics of social science research. A moral philosophy that has been relatively neglected in the domain of research ethics, virtue ethics has much to offer those who wish to go beyond the difficulties generated by the biomedical model of research ethics and positively engage with the ethics of social scientific research. As the chapters contained in this volume show, the perspective provided by virtue ethics also exhibits a certain affinity with the emerging discourse regarding research integrity. Contributors develop various facets of virtue ethics in order to illuminate a range of issues in the practice and governance of social science, including integrity, the ethics of ethical review, ethics education, and the notion of phronesis (wisdom).